ICT in Agriculture Extension and Marketing in Malawi and Mozambique - Werner, Marcel (Technical Centre for Agricultural and Rural Cooperation, 2005)
The study involved surveying agricultural and rural development stakeholders, as well as consultations among those stakeholders to bring out views on information needs and perceptions on the possible role of Information and Communication Technology (ICT).